Relationship Between Community-Based Total Sanitation and Stunting Incidence in Medan City - Retno Danthi Shafira; Irnawati Marsaulina; Evi Naria (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Stunting remains a significant public health issue in Indonesia, particularly in Medan City. Poor sanitation has been identified as one of the key contributing factors to stunting. This study aims to analyze the relationship between community-based total sanitation and stunting incidence in Medan City. The research is a comparative study with a case-control design. It was conducted in five sub-districts with high stunting rates among the fourteen sub-districts in Medan City that have received community-based total sanitation interventions. The study was carried out from November 2023 to February 2024. The study population included all mothers with children age 0-59 months living in sub-districts that received community-based total sanitation interventions. There were 165 participants in the stunting and 49,676 in the not stunting. The sample size was calculated using the Lemeshow formula, resulting in 50 mothers for the stunting group. The not stunting group was matched to the case group in a 1:1 ratio, making the total sample size 100 mothers. Purposive sampling was used to select participants who met the inclusion and exclusion criteria. Data analysis was performed using SPSS software version 27, employing the chi-square test with a 95% confidence level (α = 0.05). The results showed that three pillars of community-based total sanitation were significantly related to stunting incidence: relationship between handwashing with soap and stunting incidence was significant (p=0.005; OR=4.125), relationship between household Latrine and stunting incidence was significant (p=0.001; OR=7.211), and relationship between household solid waste management and stunting incidence was significant (p=0.027; OR=2.681). The overall relationship between community-based total sanitation and stunting incidence was significant (p=0.015; OR=6.769). Recommendations for the Health Department and Community Health Centers in Medan City include enhancing the achievement of the five STBM pillars within the community through health promotion activities. Keyword: Child, Hygiene, Mother, Sanitation, Stunting